IMPROVING COGNITIVE ABILITIES OF 4–5-YEAR-OLD CHILDREN THROUGH THE PATTERNED NUMBER HOPPING GAME - Nabila, Ulfah; Yulianty, Nadya; Enjang, (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
This classroom action research aimed to improve the cognitive abilities of 4–5-year-old children through the patterned number hopping game at TK Trisula Perwari Purwakarta. The study background was the children’s limited ability to recognize numbers, mention number sequences, and follow simple number patterns. The research used Classroom Action Research (CAR) with a descriptive qualitative approach. The subjects were 8 children in Group A (4 boys and 4 girls). The study was conducted in two cycles, each consisting of planning, action, observation, and reflection. Data were collected through observation, documentation, and field notes, and analyzed descriptively. The results showed an improvement in children’s cognitive abilities from the pre-cycle to the second cycle. In the pre-cycle, most children had difficulty recognizing numbers and following simple sequences. In the first cycle, they began to show progress but still made mistakes. In the second cycle, almost all children were able to recognize numbers, follow number sequences, and understand simple patterns correctly. The conclusion is that the patterned number hopping game is effective, simple, and enjoyable for improving early childhood cognitive abilities, especially in number recognition, sequencing, and understanding patterns.